Global research trend of sustainable transport in response to energy efficiency: A bibliometric analysis - Maryam Jamilah, Asha’ari; Salina, Daud; Kasavan, Saraswathy; Wan Mohammad Taufik, Wan Abdullah; Siti Indati, Mustapa; Rajadurai, Jegatheesan; Nurul Nadiah, Ahmad; Wan Noordiana, Wan Hanafi; Siti Norhidayah, Toolib; Mohamed Azrin, Mohamed Ali (SAGE Publications Inc, 2024)
Numerous studies have been conducted on sustainable transportation and its impact on global energy efficiency. However, the evolution and performance patterns of this field remain relatively unknown and limited. A bibliometric analysis was conducted to explore the global research trends to determine the state-of-the-art sustainable transport linked to energy efficiency over the past 21 years. The Web of Science (WoS) database was searched to explore the research related to sustainable transport in response to energy efficiency from 2002 to 2022, resulting in the identification of 2,884 articles. In this study, VOSviewer was used to analyse collaboration networks between authors, countries, institutions and cooccurrence analysis of keywords in three defined periods. The results reveal that the majority of studies on sustainable transport and energy efficiency were primarily conducted in the USA, with limited research conducted in Asian countries. The study found that the subject categories of ‘‘transport planning,’’ ‘‘transport policy,’’ ‘‘climate change,’’ ‘‘electric vehicles,’’ and ‘‘public transport’’ are the most prolific research contributors. During Phase III (2016–2022), most studies were centred around electric vehicles in the field of sustainable transportation, as opposed to Phase II (2009–2015). These findings enhance our understanding of the research landscape in this field and offer valuable insights for future studies. Future studies could examine how the latest technology enhances energy efficiency in the transportation sector and focus on the usage and benefits of hydrogen fuel cell vehicles (HFCVs).